Penggunaan Sutra untuk Terapi Penyakit bagi Laki-laki: Studi Takhrij Hadis - Rizaldi Erdin Prawira; Muhamad Yoga Firdaus; Adnan Adnan; Rifki Rosyad (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to analyze the hadith about the use of silk to treat ailments for men. The method used in this research is a qualitative method emphasizing literature study through the takhrij and syarah hadith methods with contemporary analysis. The results of the research and discussion show that the quality status of the hadith regarding the use of silk for the treatment of disease for men is considered valid based on the takhrij hadith. Moreover, the shari'ah of the hadith explains that it is permissible to use something forbidden in an urgent situation. This study concludes that silk can be used as a medicinal ingredient under certain conditions and emergencies.